The Evolution of the ESL Learner: A Review of Affective, Structural, and Cultural Hurdles from Literacy to Native-Like Fluency - Mardy Serey; Chanrathany Sam; Sannisa Seng; Toknoy San; Sam Et Ry; Soeung Sit; Sophat Phon (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This comprehensive review article synthesizes current literature on second language acquisition (SLA) to examine the primary hurdles ESL learners encounter throughout their evolutionary trajectory - from basic literacy to native-like fluency. The paper aims to provide a holistic understanding of the learner's experience and to evaluate pedagogical interventions designed to mitigate these hurdles. Methodology: The study methodology is narrative/integrative literature review. It integrates theoretical perspectives and empirical research into SLA with literature based on established theoretical models including Krashen’s Affective Filter Hypothesis, Dörnyei’s L2 Motivational Self System, Selinker’s Interlanguage Theory, the Contrastive Analysis Hypothesis, and Vygotsky’s Zone of Proximal Development. Since this methodology was conceptual and desk-based, there was no primary data collection. Main Findings: The review also finds that achieving native-like fluency requires not only cognitive and linguistic development but also profound socio-emotional adaptation. Pedagogical interventions, such as scaffolding, communicative language teaching, and translanguaging, are identified as effective strategies for mitigating these hurdles. Novelty/Originality of this study: Novelty of this paper is that it adopts a tripartite, integrative framework focusing on affective, structural, and cultural barriers in a single review — it deviates from previous studies that examine these domains in isolation. By mapping the ESL learner's entire developmental trajectory from literacy to native-like fluency through this holistic lens, the paper advocates for a novel, inclusive, culturally responsive, and psychologically supportive ESL educational framework that addresses the learner as a whole person rather than merely a linguistic processor.